The impact of school on the suicidal ideation of adolescents - Friedemann, Adams; Narvaez, Joana (Clinical Styles. The Journal on the vicissitudes of childhood, 2020)
In school, adolescents extend their social life and experience important psychic transformations, creating an environment prone to the development of psychopathological conducts, such as suicidal ideation. Through a qualitative exploratory research, we seek to comprehend the perception of adolescents regarding the implication of school in their suicidal ideation. We conducted a semi-structured interview with four adolescents, students of public schools, analyzed through the clinical-interpretative strategy. Our results show that participants do not consider school a mitigating space for their psychic suffering. The presence of a psychologist at school is important to enable the creation of new vicissitudes for adolescent conflicts.